1994
DOI: 10.1111/j.1460-9592.1994.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of pain and vomiting in paediatric day case surgery

Abstract: Summary Three hundred and thirteen paediatric day case patients were prospectively audited to assess postoperative pain, nausea and vomiting using data sheets completed by nursing staff, anaesthetists and parents. The incidence of nausea and vomiting was 7.3% and was commoner in older children and those who had received opioids. Forty per cent of patients had some degree of postoperative pain; 17% of these patients were scored as having severe pain. Of children who had pain on returning home (31.4%), 85% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
4
14
1
Order By: Relevance
“…The results indicated that 85 percent of the children slept as usual but 15 percent woke in pain. These findings are similar to other studies in that Tan et al (1994) found 15 percent of children experienced a disturbed night due to pain, whereas Ling (1996) established that 2 percent of children had a restless night due to discomfort. The high percentage of children having a complete night's sleep may have been due to the information in the leaflet, which suggested to parents that they give their child a dose of pain relief at bedtime.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicated that 85 percent of the children slept as usual but 15 percent woke in pain. These findings are similar to other studies in that Tan et al (1994) found 15 percent of children experienced a disturbed night due to pain, whereas Ling (1996) established that 2 percent of children had a restless night due to discomfort. The high percentage of children having a complete night's sleep may have been due to the information in the leaflet, which suggested to parents that they give their child a dose of pain relief at bedtime.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have previously reported circumcision as being associated with severe pain (Tan et al, 1994). In this study there were eight children who underwent circumcision with a mean age of 6.5 years; all the children undergoing circumcision received a local anaesthetic block, Paracetamol and Ibuprofen.…”
Section: Pain and Type Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…PONV has been the most important reason for unanticipated admissions [2,23], but this was not the case in our survey. The overall incidence of PONV was also relatively low, even in the case of tonsillectomy (31% compared with up to 70-80% in some studies).…”
Section: Nausea and Vomitingmentioning
confidence: 54%
“…Pain, postoperative nausea and vomiting (PONV) and the risk of bleeding should be avoided [1]. In the few studies in which follow-up covers the time after discharge, pain has been problematical in children after circumcision [2,3] and PONV has been most common after strabismus surgery and tonsillectomy [4,5]. The choice of anaesthetic technique can modify morbidity at home.…”
mentioning
confidence: 99%